The Intersection of Gender and Race in Adult Education Research - Juanita Johnson-Bailey (Adult Education Research Conference, 2010)
Across a fifteen year career, this researcher has labored to conduct research through a perspective that equally considered and honored gender and race, with an acceptance of the complex and often contested passion that recognized a universality to gender that is not consistent in the multifaceted system of race/racism. After an introduction of the two theoretical frames that have guided this researcher’s publications, this paper follows the progression of five exemplars chosen from over 100 publications: Women of Color in the Academy: Where’s Our Authority in the Classroom; Everyday Perspectives on Feminism: African American Women Speak Out; Sonia Sanchez: Telling What We Must Hear; Harriet Buckley: An Artist Storyteller; and Different Worlds and Divergent Paths: Academic Careers Defined by Race and Gender.